Is anaemia associated with dietary habits and increased menstrual bleeding - Samarakoon, D.N.A.W.; Amarathunga, A.A.M.D.D.N.; Perera, P.P.R. (My University, 2016)
Attached

Anaemia is a m ajor public health problem that has affected around 25% of the world's population. It is one o f the m ajor nutritional deficiency disorders in Sri Lanka. Objectives were to determ ine the prevalence and some factors associated w ith anaemia among female hostellers o f U niversity o f Sri Jayewardenepura. A cross-sectional study was conducted among 370 female undergraduates (20-26 years), random ly selected using blind draw method. Cyanomethaemoglobin method was perform ed. A pretested self-adm inistered questionnaire was used to retrieve inform ation on dietary habits and m enstruation. Descriptive statistics and Chi- square (02) test were used to analyze frequencies and associations. O f th e 370 fem ales, 33.6% (n=124) were anaemic (Hb<12g/dL). The corresponding p values betw een anaemia and some o f the factors were; vegetarian (P=0.055), skipping breakfast (P=0.216), daily consum ption o f dairy products (P=0.101) and animal products (P=0.103), consum ption o f at least 3 vegetables per day (P=0.091), at least 2 fruits per day (P=0.242) and at least 4 portions of green leaves per week (P=0.929) and increased menstrual bleeding (P=0.825). P roportion o f anaemia in the population did n't show a statistically significant association (P>0.05) w ith selected dietary habits and menstrual bleeding. One th ird o f th e fem ale undergraduates were anaemic. This may have an effect on their study skills and day to day activities in the University. Selected dietary habits and menstrual blood loss w e re n 't contributory factors fo r anaemia in this population. Further research should be done to determ ine the contributing factors as this population make up the future o f the country.